Management Background and Release Conditions Structure Post-release Movements in Reintroduced Ungulates - Mertes, Katherine; Stabach, Jared A.; Songer, Melissa; Wacher, Tim; Newby, John; Chuven, Justin; Al Dhaheri, Shaikha; Leimgruber, Peter; Monfort, Steven (Frontiers in Ecology and Evolution, 2019)
One of the greatest challenges in restoring threatened species to the wild is insufficient knowledge about their habitat requirements and movement ecology. This is especially true for wide-ranging species such as the scimitar-horned oryx (Oryx dammah). Once widespread across Sahelo-Saharan grasslands, oryx were declared Extinct in the Wild in 1999. Here, we integrate GPS/satellite tracking, remote sensing, and gspatial analyses into a large reintroduction project to assess how captive-born oryx respond to wild conditions. We monitored two groups of oryx, reared under different management approaches and released in different seasons, for 12 months after release. Our study provides the first movement trajectories and home range estimates ever recorded for this species. We assessed how captive management methods, release timing, and local environmental conditions during and after release affected oryx movement behavior, survival, and fecundity. Post-release dispersal ranged from 2-90 km. Oryx raised under semi-free ranging conditions, which experienced a long acclimation period, and released during the wet season (“ranging”), moved 40-60 km from the release site. In contrast, oryx raised in smaller pens, with a short acclimation period, and released during the dry season (“penned”), remained within 5-25 km. We expected oryx movements after release to represent tradeoffs between risky, energetically expensive exploratory movements, and optimal resource exploitation. Ranging oryx exhibited this predicted pattern of exploration followed by home range establishment, while penned oryx explored less novel terrain and continuously returned to the release site where supplemental food and water were available. Ranging oryx also exhibited seasonal shifts in movement patterns, while penned oryx simply reduced overall movement. Our results demonstrate that captive management and environmental conditions at release strongly influence the rate and extent to which reintroduced oryx disperse and adapt to wild conditions. We also show that – in contrast to previous studies – longer acclimation periods do not always lead to greater site fidelity. Finally, our findings demonstrate the importance of tracking the largest possible proportion of reintroduced individuals in order to: (1) accurately record post-release behaviors and vital rates of a reintroduced population and (2) adaptively evaluate pre- and post-release management actions to improve conservation outcomes.